Contribution of phages to the virulence of pathogenic mycobacteria. - Geebe, Nomakorinte (My University, 2008)
ABSTRACT Bacteriophages have been known to contribute to the bacterial phenotype through lysogenic conversion. Many virulence factors in pathogenic bacteria are phage encoded. However, it is not known whether this is true in mycobacteria. A study by Pedulla et al,(2003) looking at the genome sequences of 10 mycobacteriophages suggested that several of the identified genes may have patho-adaptive potential. Perhaps paradoxically, sequenced mycobacterial genomes revealed a paucity of recognizable prophages. To initiate any enquiry into the contribution of prophages to the relevance of mycobacterial disease, we set up some experiments to screen for the presence of prophages in Mycobacterium bovis isolates from different outbreaks. We screened 27 isolates for spontaneously induced phages by plaque assay using M. smegmatis, M. fortuitum, M.scrofulaceum, and M. kansasii and an isolate (S2) from our lab as indicator strains. However none of these formed reproducible plaques. Only three isolates formed plaques that could not be propagated on any of the indicator strains used. To address if we could enrich for induced prophages, we did some preliminary experiments to optimize prophage induction, using a known lysogen (L5). Co-culturing of a lysogen with sensitive cells was assessed at different concentrations. The result showed that there was no difference in the rate of phage released between the co-cultured and the non-spiked control cells. Since it is possible that we did not have a strain that is sensitive to M. bovis phage(s), we checked, using the L5 lysogen, if any free phage could be detected from solid culture, by Epiflourescence Microscopy (EFM). We were able to detect phage particles in a titer of 102 as determined by plaque assay with EFM. We therefore screened 16 M. bovis isolates for any free phage, using the more sensitive EFM and no inducible phages were detected. Since potential lysogens may be very stable, with minimal induction, we decided to explore a molecular approach to screen for cryptic prophages. Guessmers based on conserved regions in the L5 repressor, shared by other phage genomes were designed .Out of 45 M .bovis isolates screened by PCR, nine produced DNA bands of different sizes from each isolate. The sequences from the L5-M. smegmatis mc2155 lysogen positive control were confirmed to be of the gp71 origins (L5 phage repressor). Sequences from clone DNA from two isolates revealed existence of different M. bovis AF2122/97 DNA specific binding proteins such as putative transposases of the IS1553 element (Mb2968) , DNA helicases (Mb0884), transcriptional regulators (Mb1160), and other M. bovis proteins such as CTP synthetase (Mb 1725), spermidine synthetase (Mb2632), and a hypothetical protein Mb1618c. Interestingly, a sequence DLLIRVNE which is conserved in L5 and other mycobacteriophage repressor proteins was also conserved in some of the M. bovis DNA binding proteins. Hence this protein might play an important role in DNA binding. An in-depth analysis of the whole genome of M. bovis is needed in order to conclude if this sequence is of prophage origin.